Pre-Transplant Aerobic Capacity and Prolonged Hospitalization After Liver Transplantation - Mancuzo,Eliane Viana (2015)
Introduction: Patients with end stage liver disease (ESLD) referred for liver transplantation (LT) are forwarded to pulmonary evaluation before being operated. ESLD is associated with muscle wasting, reduced exercise tolerance and aerobic capacity. Objectives: We assessed the association between aerobic capacity (AC), liver disease severity and postoperative LT outcomes in a series of LT candidates in a university affiliated hospital in Brazil. Methods: Pre-LT oxygen uptake at peak (pre-VO2peak), liver disease severity, and early pos-LT outcomes such as length of intensive care unit (ICU) stay, <5 and ≥5 days and hospitalization, <20 and ≥20 days and postoperative mortality were compared. Pre-VO2peak was measured through the cardiopulmonary exercise testing (CPET). Severity of liver disease was estimated by the Model for End-Stage Liver Disease (MELD) categorization into MELD < 18 and MELD≥18 groups. Students t-test was used to compare these groups. A logistic regression model was built to verify the effect of those variables on the length of ICU stay, length of hospitalization and postoperative mortality. Results: A total of 47 patients were include in analysis. Pre-VO2peak was similar to that of healthy sedentary individuals (75±18%) and worse in the MELD≥18 group as compared to the MELD < 18 group (19.51±7.87 vs 25.21±8.76 mL/kg/min, respectively; p = 0.048). According to the multivariate analysis, only a lower pre-VO2peak (<20.09±4.83 mL/kg/min) was associated to a greater length of hospitalization (p = 0.01). Conclusions: In LT candidates, a reduced pre-VO2peak may predict a higher risk of greater pos-LT length of hospitalization. The length of ICU stay and postoperative mortality were not associated with variables studied. This finding should be evaluated in other studies before making specific recommendations about a routine use of CPET in LT candidates.